Invasive Fungal Infection in Hematopoietic Stem Cell Transplant Recipient from an Indian Oncology Setting - Ghafur, Abdul; Das, Bikram; Raja, T.; Easow, Jose; Kartikeyan, Radhika; Easow, Benjamin M.; Ramanan, S G. (South Asian Journal of Cancer, 2023)
Objective Invasive fungal infections (IFI) are one of the major causes of morbidity and mortality in post-hematopoietic stem cell transplant (HSCT) recipients. Data from India is limited. The objective of this study was to analyze the incidence, risk factors, and outcomes associated with IFI in our center.Materials and Methods Adult patients, who underwent marrow/stem cell transplantation between 2014 and 2018, in an oncology center in India, were included in this single-center retrospective observational study. The revised European Organization for Research and Treatment of Cancer/ Mycoses Study Group (EORTC/MSG) consensus group 2008 definition for IFI was considered to define cases. Incidence, risk factors, and outcomes associated with IFI were analyzed.Statistical Analysis All continuous variables were represented by mean ± standard deviation and categorical variables as percentage. Comparison of categorical variables was done by either the chi-squared test or Fisher's exact test. All “p” values less than 0.05 were considered statistically significant.Results Out of the 126 patients who underwent HSCT between January 2014 and December 2018, 56 (44.4%) patients had allo-HSCT, 64 (50.8%) had auto-HSCT, and 6 (4.8%) had haplo-identical HSCT. Eighty-three (63%) patients were male and 43 (34%) females, and 113 (83.9%) Asians and 13 (10.3%) Africans. Total 111 (88%) patients received myeloablative conditioning and 24 (19%) received total body irradiation. The hematological conditions were acute myeloid leukemia (n = 23; 18.25%), acute lymphoblastic leukemia (n = 16; 12.69%), chronic myeloid leukemia (n = 4; 3.17%), Hodgkin lymphoma (n = 17; 13.4%), non-Hodgkin lymphoma (n = 11; 8.73%), myeloma (n = 35; 27.7%), sickle cell disease (n = 13; 10.31%), etc. Most patients received fluconazole (78; 61.9%) followed by micafungin (23; 18.25%), posaconazole (20; 15.87%), voriconazole (4; 3.17%), and liposomal amphotericin B (1; 0.79%) as antifungal prophylaxis. The overall rate of IFI (possible cases included) was auto-HSCT (n = 5; 7.81%), and allo-HSCT (n = 5; 8.92%). Among auto-HSCT, the IFI was proven = 0, probable n = 1 (1.5%), and possible n = 4 (6.25%) and among allo-HSCT the IFI was proven = 0, probable n = 2 (3.57%), and possible n = 3 (5.35%). No patients in haplo-HSCT had IFI. The 1-year survival rate among the IFI cases was 8/10(80%). A meaningful comparison of the risk factors and the impact of prophylactic regimens were difficult because of the very low number of IFI cases.Conclusion The overall rate of IFI in HSCT patients in our setting was low compared to global data on IFI in HSCT.
Keywords: hematopoietic stem cell transplant; India; invasive fungal infection; antifungal prophylaxis